(untitled) (Journal of the College of Basic Education, 2022)
The research focused on showing the role of the Sudanese depression in precipitation. Iraq for ten rainy seasons (1990/2000-1991/1999) and for four stations distributed on the study area, and the research concluded that the frequency of the Sudanese depression varies between the months and seasons of the study, the lowest recorded the highest frequency during the month of March and the lowest during The month of October, and its highest hourly frequency was during the daytime observation, as the radiation The solar is responsible for its appearance, as was its frequency during the transitional seasons (autumn and spring) with little or no rain, while its recurrence during the winter months was mostly